Implementation of Quality Management System to Improve Electricity Efficiency - Munaiseche, Maya E.I; Mamangkey, Ekleysia; Molano, Naldo Sebastian; Sengkey, Claudya; Sasela, Adrianus Ficky (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The increasing global demand for electricity coupled with environmental sustainability concerns has created significant challenges in electrical energy management. The quality of electricity management plays a major role in ensuring optimal energy efficiency. One approach that can be applied is through a quality management system (QMS). This study aims to analyze how the implementation of QMS, specifically through ISO 9001 and ISO 50001 standards, can systematically improve electricity efficiency in production, distribution, and energy consumption processes, while enhancing environmental sustainability through reduced carbon emissions. The research methodology employs comprehensive literature review and secondary data analysis from multiple sources including industry reports, case studies of electricity companies that have implemented QMS, and evaluation of operational efficiency indicators and energy savings data from various international sources. This approach not only helps in terms of operational efficiency, but also contributes to environmental sustainability by reducing carbon emissions resulting from excessive energy consumption. The research findings demonstrate that companies implementing ISO 9001 and ISO 50001 standards achieve remarkable improvements: operational efficiency increases with up to 20% reduction in distribution network disruptions, 15% reduction in electricity consumption through optimized systems, 25% reduction in equipment failure rates through predictive maintenance, and 18% reduction in operational costs over five years. The implications of this research indicate that QMS implementation not only provides immediate operational benefits but also establishes a foundation for long-term sustainability in the electricity sector. In conclusion, the implementation of QMS not only helps electricity companies improve energy efficiency but also supports environmental sustainability.